Seeing Things Their Way; IntellectualHistory and the Return of Religion. - Pointer, Steven R. (Fides et historia, 2011)
The article reviews the book "Seeing Things Their Way: Intellectual History and the Return of Religion" edited by Alister Chapman, John Coffey, and Brad S. Gregory.